FREQUENCY OF CERVICAL RIBS AMONG ADULT MALES SEEKING EMPLOYMENT IN PAKISTAN ARMY - Arshad, Muhammad; Hameed, Jawaid; Sahi, Amer Zamir (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of cervical ribs among adult male population seeking employment in Pakistan army.Study Design: Cross sectional study.Place and Duration of Study: Department of Diagnostic Radiology, Combined Military Hospital, Hyderabad cantt from 1st October 2012 to 31st March 2014.Material and Methods: The study was conducted on chest radiographs of 4337 adult males who reported for recruitment in Pakistan Army irrespective of ethnicity.Results: The prevalence of cervical ribs among adult males of Pakistan was 6.11% with 4.29% bilateral, 1.13% right sided and 0.69% on left side.Conclusion: Pakistani adult male population was observed to have 6.11% prevalence of cervical ribs, thus justifying initial screening chest radiographs of all candidates for military recruitment that can pick up all cases of cervical ribs in addition to exclusion of cardiopulmonary pathologies.